2012
DOI: 10.4028/www.scientific.net/jbbte.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigations of the Sandfish’s β-Keratin (Reptilia: Scincidae: <i>Scincus scincus</i>). Part 1: Surface and Molecular Examinations

Abstract: The Sandfish (Scincidae: Scincus Scincus) Is a Lizard Capable of Moving through Desert Sand in a Swimming-Like Fashion. the Epidermis of this Lizard Shows a High Resistance against Abrasion Together with a Low Friction to Sand as an Adaption to a Subterranean Life below the Desert’s Surface, Outperforming even Steel. the Low Friction Is Mainly Caused by Chemical Composition of the Scales, which Consist of Glycosylated β-Keratins. in this Study, the Friction, the Micro-Structure, the Glycosylation of the β-Kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Therefore, a direct comparison between the avian sequences and the reptilian sequences was not possible. When the gene structure and primary sequences of reptilian betakeratins became known for the first time in lizards and snakes (Dalla Valle et al 2005, and later in the remaining nonavian sauropsids (Dalla Valle et al , 2009aValle et al , b, 2010Hallahan et al 2008;Ye et al 2010;Staudt et al 2012), and the colocalization with alpha-keratins was shown (Alibardi 2012(Alibardi , 2013a(Alibardi -e, 2015, the new interpretation outlined above on the process of cornification in sauropsids was strengthened. This interpretation indicates that the so-called beta-keratins represent the more abundant class of nonkeratin proteins of sauropsids that associate to keratins as "keratin-associated beta-proteins" (KABPs) or as "corneous beta-proteins" (CBPs).…”
Section: Beta-keratins Are Sauropsid Corneous Beta-proteinsmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, a direct comparison between the avian sequences and the reptilian sequences was not possible. When the gene structure and primary sequences of reptilian betakeratins became known for the first time in lizards and snakes (Dalla Valle et al 2005, and later in the remaining nonavian sauropsids (Dalla Valle et al , 2009aValle et al , b, 2010Hallahan et al 2008;Ye et al 2010;Staudt et al 2012), and the colocalization with alpha-keratins was shown (Alibardi 2012(Alibardi , 2013a(Alibardi -e, 2015, the new interpretation outlined above on the process of cornification in sauropsids was strengthened. This interpretation indicates that the so-called beta-keratins represent the more abundant class of nonkeratin proteins of sauropsids that associate to keratins as "keratin-associated beta-proteins" (KABPs) or as "corneous beta-proteins" (CBPs).…”
Section: Beta-keratins Are Sauropsid Corneous Beta-proteinsmentioning
confidence: 86%
“…1S A and C). Other studies on the sandfish lizard have evidenced that some betaproteins can also be glycosylated, a process that has been put in relation to the formation of a beta-layer adapted to lower the friction with the ground where this species is adapted to dig, borrow, and move (Staudt et al 2012). …”
Section: Proteome Studiesmentioning
confidence: 97%
“…A recent study on beta‐proteins of the sandfish lizard, a species that is adapted to dig and move in the sand, has suggested that beta‐keratin can be glycosylated, further extending possible roles for these small structural proteins (Staudt et al . ,b). The latter study indicates that glycosylation of beta‐keratins occurs prevalently in the sandfish lizard although, in other species not adapted to the sand environment, beta‐keratins also appear to contain a lower amount of glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…; Staudt et al . ). These studies have indicated that sauropsid beta‐keratins are the analogous proteins indicated in mammals as KAPs, and they are now indicated as ‘keratin‐associated beta‐proteins’ (KAbetaPs) or simply beta‐proteins.…”
Section: Introductionmentioning
confidence: 97%
“…Possible inspiration comes from snake-skins having surface features enabling low friction in a preferred moving direction [2]. For example sand-swimming reptiles, like the sandfish, have micro-structures on there skin that allow them, in combination with the biochemical composition of the structures, to move in sand with very low friction [3]. Shark denticles are also developed by nature to reduce the fluid-drag in water [4].…”
Section: Introductionmentioning
confidence: 99%